A rare case of Bardet-Biedl syndrome in a 10 years old child with clinical and genetic correlation - Salwa, Zeena; Rahman, M. Sajedur; Tanzim, Tanha (International Journal of Contemporary Pediatrics, 2026)
Bardet–Biedl syndrome (BBS) is a rare autosomal recessive ciliopathy characterized by multisystem involvement, including rod–cone dystrophy, polydactyly, obesity, genital anomalies, renal dysfunction, and neurodevelopmental delay. We report a 10-year-old boy who presented with night blindness, progressive visual impairment, obesity, polydactyly, acanthosis nigricans, and insulin resistance. Ophthalmological evaluation revealed reduced visual acuity with bilateral optic disc pallor. The constellation of clinical features fulfilled the diagnostic criteria for Bardet–Biedl syndrome and was subsequently confirmed by genetic testing. Early clinical recognition of BBS is crucial to ensure timely multidisciplinary management and appropriate genetic counseling. This case underscores the importance of considering syndromic etiologies in children presenting with visual impairment, obesity, and polydactyly to facilitate prompt diagnosis and intervention.